Effects of L-Arginine Supplementation on Lactating Mares and the Development of Foals - Hunka, Monica Miranda; Silva, Elizabeth Regina Rodrigues da; Kutschenko, Marianne; Nogueira, Eduardo Terra; Manso, Helena Emília Cavalcanti da Costa Cordeiro; Filho, Hélio Cordeiro Manso (Acta Scientiae Veterinariae, 2016)
Background: Most animal species are able to produce Arginine (Arg) under normal conditions. However, in some situations, its degradation can be higher than its production. For example, during a period of lactation or disease, there is an increase in the consumption of Arg. In this case, endogenous production is not enough for the animal’s demands. Indeed, Arg supplementation in animals has several benefits for the animal’s body, such as the increase of angiogenesis, improvements in immunity and the reproductive system, as well as the stimulation of lactogenesis. During the early phase of growth, a deficiency of Arg could cause a reduction in the growth rate and metabolic activity of animals. Therefore, this amino acid is considered essential in some phases of the life of animals. However, very few studies of the supplementation of this amino acid in horses have been carried out. The aim of the present study was to characterize the effects of supplementing lactating mares and their foals with Arg. Materials, Methods & Results: Lactating mares (n = 10) were divided into two groups (control group: n = 3 / supplemented group: n = 7) and maintained exclusively under grazing. The supplemented group received 50 g of Arg during the lactation period. Samples of milk and blood from mares and blood from foals were collected at different phases of the lactation period. The following parameters were measured in milk: Glutamine (Gln); Glutamate (Glu); protein; fat; casein; lactose; urea and total solids. The following parameters were measured in blood: Gln; Glu; total plasmatic protein (TPP); albumin; urea; creatinine; uric acid; triglycerides; total cholesterol; calcium (C); phosphorous (P); magnesium (Mg) and ferrous (Fe). In addition, the biometric parameters of Wither Height (WH), Chest Perimeter (CP), Cannon Bone Circumference (CBC) and Fat Percentage (FP) of foals were obtained. A significant increase of Gln was observed in the milk in both groups (P < 0.05). The highest concentration of Gln was detected in the third month of the lactation period in the supplemented group (~ 2.26 mmol/mL), and the control group (~ 1.91 mmol/mL) during the same period. Gln did not alter in the blood (P > 0.05), although Glu was higher in the control group in the first month of the lactation period (~ 0.21 mmol/mL) (P < 0.05). An increase in uric acid (~ 0.19 mmol/L) in both groups on the day of birth (P < 0.05). In the supplemented group, increases in triglycerides (~ 0.60 mmol/L), Ca (~ 2.90 mmol/L) and Mg (~ 0.52 mmol/L) were observed in the first month of the lactation (P < 0.05). At birth, foals exhibited high levels of urea (~ 4.67 mmol/L) and uric acid (~ 0.21 mmol/L), and low levels of P (~ 2.02 mmol/L) (P < 0.05). The levels of Gln in the blood of foals remained between 0.50 and 0.70 mmol/mL throughout the lactation period (P > 0.05). Even when they were added (Gln + Glu), no differences were observed (P > 0.05). However, when the biometric parameters were analyzed, significant variations were detected in almost all characteristics (weight, WH, CP and CBC). In particular, the control group exhibited higher body mass and CP in the fifth month, when compared with the group of foals born from supplemented mares (P < 0.05). The FP did not alter in either of the groups analyzed (P > 0.05). Discussion: The results indicate that the supplementation of lactating mares with Arg produced few alterations in the parameters analyzed for both mares and foals. In addition, the supplementation did not produce side effects among the supplemented animals.